The cost of influenza in Thailand - Simmerman, James Mark; Lertiendumrong, Jongkol; Dowell, Scott F.; Uyeki, Timothy; Olsen, Sonja J.; Chittaganpitch, Malinee; Chunsutthiwat, Supamit; Tangcharoensathien, Viroj (Vaccine, 2006)
The cost of influenza in less wealthy tropical countries is needed to inform national vaccine policy decisions. Between September 2003 and August 2004, we prospectively identified hospitalized pneumonia cases and outpatients with laboratory confirmed influenza in a Thai province. Disease incidence, patient interviews, medical record reviews, and data from a national health survey were used to calculate direct and indirect costs which were extrapolated to the Thai population. Influenza was identified in 80 (11%) of 761 hospitalized pneumonia inpatients with projected annual incidence of 18–111/100,000 population. Influenza was confirmed in 23% of 1092 outpatients with an estimated annual incidence of 1420/100,000 population. Influenza was estimated to cause between US$ 23.4 and US$ 62.9 million in economic losses with lost productivity accounting for 56% of all costs. The burden of influenza in Thailand is greater than previously appreciated, particularly in young children and the elderly. The impact and cost-effectiveness of influenza vaccination for high-risk groups merits further investigation.